2014
DOI: 10.1002/2013jd021065
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐biennial oscillation and solar cycle influences on winter Arctic total ozone

Abstract: The total column ozone (TCO) observed from satellites and assimilated in the European Centre for Medium-Range Weather Forecasts since 1979 is used as an atmospheric tracer to study the modulations of the winter Arctic stratosphere by the quasi-biennial oscillation (QBO) and the solar cycle. It is found that both the QBO and solar forcings in low latitudes can perturb the late winter polar vortex, likely via planetary wave divergence, causing an early breakdown of the vortex in the form of sudden stratospheric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 86 publications
0
18
0
Order By: Relevance
“…Enhanced ascent of air in the tropics enhances ozone levels in the high equatorial and midlatitude stratosphere during easterly QBO and late winter [see, e.g., Randel and Cobb , , Figure 11; Baldwin and Dunkerton , , Figure 23]. It also enhances ozone content in the high latitudes especially during late winter [ Li and Tung , ]. Bowman [] showed that the QBO strongly anticorrelates with the amount of ozone in polar regions between 70 and 90°N in late winter (February–April).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced ascent of air in the tropics enhances ozone levels in the high equatorial and midlatitude stratosphere during easterly QBO and late winter [see, e.g., Randel and Cobb , , Figure 11; Baldwin and Dunkerton , , Figure 23]. It also enhances ozone content in the high latitudes especially during late winter [ Li and Tung , ]. Bowman [] showed that the QBO strongly anticorrelates with the amount of ozone in polar regions between 70 and 90°N in late winter (February–April).…”
Section: Discussionmentioning
confidence: 99%
“…TOC variations can also be caused by changes in the surface climate ). Other studies have reported the effects of internal climate variability on ozone, including phenomena such as the Madden-Julian oscillation (e.g., Fujiwara et al 1998;Tian et al 2007; C. Weare 2010;Li et al 2012;Y. Zhang et al 2015), El Niño-Southern Oscillation (ENSO) (e.g., Ziemke and Chandra 1999;Cagnazzo et al 2009;Randel et al 2009;Xie et al 2014a,b;J.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 2015), El Niño-Southern Oscillation (ENSO) (e.g., Ziemke and Chandra 1999;Cagnazzo et al 2009;Randel et al 2009;Xie et al 2014a,b;J. Zhang et al 2015a,b), the quasi-biennial oscillation (e.g., Angell and Korshover 1973;Bowman 1989;Tung and Yang 1994;Dhomse 2006;Li and Tung 2014), and the Arctic Oscillation (AO) or North Atlantic Oscillation (NAO) (e.g., Appenzeller et al 2000;Schnadt and Dameris 2003;Lamarque and Hess 2004;Creilson et al 2005;Steinbrecht et al 2011). In fact, quantification of this internally driven ozone variability forms a key part of the assessment of the performance of chemistryclimate models (CCMs).…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of ultraviolet (UV) to TSI are relatively small, i.e., less than 10% (Krivova et al 2006), but the UV portions of the solar irradiance are quite variable and extremely important to Earth's middle atmosphere through photochemical processes (Haigh 2007;Gray et al 2010;Haigh et al 2010;Merkel et al 2011;Swartz et al 2012;Ermolli et al 2013;Wen et al 2013;Li & Tung 2014;and references therein). Solar cycle driven modulations of Arctic and North Atlantic Oscillations (AO/NAO) by the state of the stratosphere have been addressed in many previous works (Shindell et al 2001;Kodera 2002;Lee & Hameed 2007;Lee et al 2008;and references therein).…”
Section: à2mentioning
confidence: 99%